Genes in a Refined Smith-Magenis Syndrome Critical Deletion Interval on Chromosome 17p11.2 and the Syntenic Region of the Mouse - Bi, Weimin (Cold Spring Harbor Laboratory Press, 2002)
Smith-Magenis syndrome (SMS) is a multiple congenital anomaly/mental retardation syndrome associated with behavioral abnormalities and sleep disturbance. Most patients have the same ∼4 Mb interstitial genomic deletion within chromosome 17p11.2. To investigate the molecular bases of the SMS phenotype, we constructed BAC/PAC contigs covering the SMS common deletion interval and its syntenic region on mouse chromosome 11. Comparative genome analysis reveals the absence of all three ∼200-kb SMS-REP low-copy repeats in the mouse and indicates that the evolution of SMS-REPs was accompanied by transposition of adjacent genes. Physical and genetic map comparisons in humans reveal reduced recombination in both sexes. Moreover, by examining the deleted regions in SMS patients with unusual-sized deletions, we refined the minimal Smith-Magenis critical region (SMCR) to an ∼1.1-Mb genomic interval that is syntenic to an ∼1.0-Mb region in the mouse. Genes within the SMCR and its mouse syntenic region were identified by homology searches and by gene prediction programs, and their gene structures and expression profiles were characterized. In addition to 12 genes previously mapped, we identified 8 new genes and 10 predicted genes in the SMCR. In the mouse syntenic region of the human SMCR, 16 genes and 6 predicted genes were identified. The SMCR is highly conserved between humans and mice, including 19 genes with the same gene order and orientation. Our findings will facilitate both the identification of gene(s) responsible for the SMS phenotype and the engineering of an SMS mouse model.